CD40 promotes MHC class II expression on adipose tissue macrophages and regulates adipose tissue CD4+ T cells with obesity. Issue 6 (11th December 2015) - Morris, David L.; Oatmen, Kelsie E.; Mergian, Taleen A.; Cho, Kae Won; DelProposto, Jennifer L.; Singer, Kanakadurga; Evans‐Molina, Carmella; O'Rourke, Robert W.; Lumeng, Carey N.
Abstract : CD40‐deficient mice fail to induce conventional CD4 + cells in adipose tissue associated with decreased markers of antigen presentation in ATMs. Abstract : Obesity activates both innate and adaptive immune responses in adipose tissue, but the mechanisms critical for regulating these responses remain unknown. CD40/CD40L signaling provides bidirectional costimulatory signals between antigen‐presenting cells and CD4 + T cells, and CD40L expression is increased in obese humans. Therefore, we examined the contribution of CD40 to the progression of obesity‐induced inflammation in mice. CD40 was highly expressed on adipose tissue macrophages in mice, and CD40/CD40L signaling promoted the expression of antigen‐presenting cell markers in adipose tissue macrophages. When fed a high fat diet, Cd40 ‐deficient mice had reduced accumulation of conventional CD4 + T cells (Tconv : CD3 + CD4 + Foxp3 − ) in visceral fat compared with wild‐type mice. By contrast, the number of regulatory CD4 + T cells (Treg : CD3 + CD4 + Foxp3 + ) in lean and obese fat was similar between wild‐type and knockout mice. Adipose tissue macrophage content and inflammatory gene expression in fat did not differ between obese wild‐type and knockout mice; however, major histocompatibility complex class II and CD86 expression on adipose tissue macrophages was reduced in visceral fat from knockout mice. Similar results were observed in chimeric mice with hematopoietic Cd40 ‐deficiency. Nonetheless, neither whole body nor hematopoietic disruption of CD40 ameliorated obesity‐induced insulin resistance in mice. In human adipose tissue, CD40 expression was positively correlated with CD80 and CD86 expression in obese patients with type 2 diabetes. These findings indicate that CD40 signaling in adipose tissue macrophages regulates major histocompatibility complex class II and CD86 expression to control the expansion of CD4 + T cells; however, this is largely dispensable for the development of obesity‐induced inflammation and insulin resistance in mice.